Analisis Implementasi Media Gambar dalam Pembelajaran Pendidikan Agama Islam di SDMT Ponorogo - Latifah Kurnia Utami; Nur Kolis; Mukhibat Mukhibat (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This research aims to determine the application of image media as a learning medium in Islamic Religious Education subjects at elementary school level, especially for grade 1 students, to find out how image media can increase student participation and concentration, image media can influence students' motivation and interest in learning, and the effectiveness of their use. image media in the learning process. The method in this research is qualitative with a descriptive approach. Data collection techniques use interview, observation and documentation techniques. The data analysis technique uses the theory of Miles Huberman and Saldana, namely through the stages of data condensation, data presentation, and drawing conclusions/verification. The results of the research show that the application of image media as a learning medium in Islamic Religious Education subjects is very much needed. The application of image media is especially needed when teaching first grade students. Image media can increase student participation in learning activities, increase student concentration during the learning process. Image media also greatly influences student motivation and interest. With image media, students will not feel bored or fed up when learning takes place. So that image media is effectively used in the learning process.